Dyslipidemia after pediatric renal transplantation: the impact of immunosuppressive regimens - Habbig, Sandra; Krupka, Kai; Höcker, Britta; Tönshoff, Burkhard (Pediatric transplantation, 2017)
Dyslipidemia contributes to cardiovascular morbidity and mortality in pediatric transplant recipients. Data on prevalence and risk factors in pediatric cohorts are, however, scarce. We therefore determined the prevalence of dyslipidemia in 386 pediatric renal transplant recipients enrolled in the CERTAIN registry. Data were obtained before and during the first year after RTx to analyze possible non-modifiable and modifiable risk factors. The prevalence of dyslipidemia was 95% before engraftment and 88% at 1 year post-transplant. Low estimated glomerular filtration rate at 1 year post-transplant was associated with elevated serum triglyceride levels. The use of TAC and of MPA was associated with significantly lower concentrations of all lipid parameters compared to regimens containing CsA and mTORi. Immunosuppressive regimens consisting of CsA, MPA, and steroids as well as of CsA, mTORi, and steroids were associated with a three- and 25-fold (P<.001) increased risk of having more than one pathologic lipid parameter as compared to the use of TAC, MPA, and steroids. Thus, amelioration of the cardiovascular risk profile after pediatric RTx may be attained by adaption of the immunosuppressive regimen according to the individual risk profile.